Sustainable behaviour and social media: a study of centennials attitudes towards sustainable advertising. (22nd October 2021) - Aggarwal, Vivek; Yadav, Prashant Dev; Singh, Vinod Kumar; Dash, Snigdha
Eco-friendliness, recyclable properties, natural ingredients, association with charity or a social cause are the new characteristics of a products that influencing the purchase of consumer products in India. With increase in spending and demand for sustainable products there is need to understand ways to encourage sustainable thought and behaviour effectively and social media can be one of them. The purpose of this study is found out the significance of social media and sustainability advertising on the sustainable behaviour of young consumers aged 15 years to 25 years in India. The quantitative data was collected by means of online survey using self-administered structured questionnaires in India. A generalised linear model using structure equation modelling was used to evaluate the responses of 514 undergraduate and graduate students. The results revealed that advertising on social media has a positive influence on the behavioural intention and sustainable behaviour of young consumers. Based on findings, paper provides insights about understanding of sustainability to this population and specific design principles for creating effective social media campaigns such that more sustainable behaviours are palatable to individuals of varying attitudes.